2009
DOI: 10.1002/anie.200904024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Tetrasubstituted Alkenes by an Asymmetric Cascade Reaction Catalyzed Cooperatively by Cationic Rhodium(I) and Silver(I) Complexes

Abstract: Fantastic four: Tetrasubstituted alkenes have been prepared with high enantioselectivity by the title transformation. This reaction was successfully applied to the enantio‐ and diastereoselective synthesis of tetrasubstituted helical alkenes possessing both central and helical chirality (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Many successful examples have been reported of the former rhodium catalyzed annulation reactions initiated by aldehyde C H bond activation, 2, 6 10,24,26,28,30 while only a few examples have been reported for the latter rhodium catalyzed annulation initiated by alkyne triple bond activation. 22,32 It is worthy of note that the present novel asymmetric annulation reaction described in section 5 32 utilized the multifunctional character of the cationic rhodium(I) catalyst, which enabled the π bond activation, C H bond activation, and metallacycle formation sequence, 35 although assistance of the silver(I) catalyst was necessary. Future work will focus on further utilization of the multifunctional character of the cationic rhodium(I) catalyst for the development of novel organic reactions using functionalized benzaldehyde derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many successful examples have been reported of the former rhodium catalyzed annulation reactions initiated by aldehyde C H bond activation, 2, 6 10,24,26,28,30 while only a few examples have been reported for the latter rhodium catalyzed annulation initiated by alkyne triple bond activation. 22,32 It is worthy of note that the present novel asymmetric annulation reaction described in section 5 32 utilized the multifunctional character of the cationic rhodium(I) catalyst, which enabled the π bond activation, C H bond activation, and metallacycle formation sequence, 35 although assistance of the silver(I) catalyst was necessary. Future work will focus on further utilization of the multifunctional character of the cationic rhodium(I) catalyst for the development of novel organic reactions using functionalized benzaldehyde derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…24 Interestingly, when the reaction of 2 cyclohex 1 enylethynylbenzaldehyde and N methylisatin was conducted at room temperature in the presence of the cationic rhodium(I)/ Walphos (R,R) 2 catalyst, the unexpected benzopyranone 7a, possessing a tetrasubstituted alkene moiety, was obtained along with the expected spirocyclic benzopyranone 6a (Scheme 16). 32 Screening of chiral ligands revealed that the use of Walphos (R,R) 8 furnishes 7a in almost quantitative yield and high enantiomeric excess (Scheme 16). However the reactions of 2 alkynylbenzaldehydes possessing an alkyl, isoprope- nyl, or aryl group at the alkyne terminus with N methylisatin in the presence of the cationic rhodium(I)/(R,R) 2 or (R,R) 8 catalyst furnished spirocyclic benzopyranones as the sole products.…”
Section: Annulation Reaction Of 2 Alkynylbenzaldehydes With Carbonyl mentioning
confidence: 99%
See 3 more Smart Citations